Menjadi Muslim Barat atau Muslim Asia? - Supratman, Frial Ramadhan (Masyarakat Sejarawan Indonesia, 2017)
On 1955, the Republic of Turkey sent their delegation to participate in the Bandung Conference. What is striking, before and during their participation, was persistent distrust and reservations of Turkish delegation to the aims and purposes of Bandung Conference. The convenational explanation about this attitude is mainly provided by analyses that put the rationale to Cold War environment and Turkey position as NATO member. By highlighting the discourse surrounding Turkey participation before and during the conference, and analyzed the issue into the framework of global historical context, this paper argues that the delegation's reservations and distrust toward Bandung Conference was not merely a product of her contemporary position as NATO member and Cold War politics, but had a deeper intellectual roots in the intellectual development of Turkey elite groups when it was stiil under Ottoman state. The main point of their position was because Turkey considered themselves not as Asian Muslim, but rather identifying themselves as Western Muslim. This position have become a crucial aspect that shaped the mental outlook of Turkish position in the conference.